KEPEMIMPINAN KEPALA MADRASAH DALAM MEMANAJEMEN KURIKULUM TENAGA PENDIDIK DI KOTA MADIUN - Karoso, Subianto (Fakultas Tarbiyah dan Keguruan UIN Antasari, 2020)
Curriculum is defined as the subjects taught in schools, or it can also be interpreted that the curriculum is a teaching plan that will be addressed to students. The ability to manage the curriculum is a process carried out by someone where he organizes and organizes all activities in the school, one of which is learning. However good the implementation of learning, it depends on the educator himself who is the giver of lessons or knowledge. The results showed that the leadership of the madrasah principal in improving the ability of curriculum management by educators in Madiun City had a democratic leadership style and had the roles of educator, leader, innovator, motivator, administrator and supervisor. The stages in curriculum management include curriculum planning, curriculum implementation and curriculum evaluation.